2014
DOI: 10.2133/dmpk.dmpk-13-rg-114
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Rifampicin-induced MicroRNA and Gene Expression Changes in Human Hepatocytes

Abstract: MicroRNAs (miRNAs) post-transcriptionally regulate mRNA expression, controlling global cell function. Altered expression or function of miRNAs causes various diseases. Chemically induced changes in miRNA expression in human tissues are not fully understood. We investigated the changes in miRNA expression by rifampicin, which modulates the expression of various genes related to drug metabolism and pharmacokinetics, in human hepatocytes, and evaluated the relationship with the gene expression changes. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
(34 reference statements)
1
18
1
Order By: Relevance
“…In two studies, it was demonstrated that rifampicin may alter miRNA expression in human hepatocyte cultures [44, 45]. Apart from those studies, there are no studies available that display the role of antibiotics with regards to changes in miRNA expression in other cells in vitro or in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, it was demonstrated that rifampicin may alter miRNA expression in human hepatocyte cultures [44, 45]. Apart from those studies, there are no studies available that display the role of antibiotics with regards to changes in miRNA expression in other cells in vitro or in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, altered levels of miRNAs have been linked to liver injury induced by acetaminophen [113], rifampicin [114], and halothane [115], cardiotoxicity induced by doxorubicin [116] and bevacizumab [117], and nephrotoxicity induced by gentamicin [118,119] and cisplatin [120].…”
Section: Other Pharmaceuticalsmentioning
confidence: 99%
“…Rifampin-induced miRNA expression changes are correlated with rifampin treatment changes in PXR and P450 [6,[10][11][12]. MiRNA can indirectly influence rifampin-induced drug deposition through gene regulation [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rifampin-induced miRNA expression changes are correlated with rifampin treatment changes in PXR and P450 [6,[10][11][12]. MiRNA can indirectly influence rifampin-induced drug deposition through gene regulation [11,[13][14][15]. Proteins are synthesized from mRNA templates through a highly conserved process, many studies have reported that the functions of miRNAs can be understood by analyzing miRNAs-regulated mRNA-related PIN [16][17][18].…”
Section: Introductionmentioning
confidence: 99%